СТРУКТУРУВАННЯ ПЕДАГОГІЧНИХ ЗНАНЬ У ПРОЦЕСІ ПІДГОТОВКИ СТУДЕНТІВ ДО ПРОХОДЖЕННЯ ЛІТНЬОЇ ПЕДАГОГІЧНОЇ ПРАКТИКИ (Педагогіка вищої та середньої школи, 2007)
The object, tasks, content of student's summer pedagogical practice are exposed in the article. It was considered the structure of pedagogical knowledge at process of student's training for summer pedagogical practice.